High-temperature-resistant UV curing resin and preparation method thereof

By using materials such as acrylic resin, polyurethane acrylate and modified acrylic resin, and adding reinforced fillers and other components, a high-temperature UV curing resin is prepared, which solves the problems of the resin being prone to discoloration, neck, cracking and insufficient adhesion at high temperatures, and achieves better high-temperature and adhesion properties.

CN119592205AActive Publication Date: 2025-03-11NANXIONG YALTON CHEM CO LTD

Patent Information

Application Number
CN202411840015.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-11
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

UV curing resin is prone to discoloration, neck, cracking in high temperature environments, and lacks adhesion, which affects product quality and appearance.

Method used

A high temperature resistant UV curing resin is prepared by using acrylic resin, polyurethane acrylate and modified acrylic resin as the substrate, and reinforcement fillers, photoinitiators, defoaming agents and leveling agents are added to prepare a high-temperature resistant UV curing resin through specific mixing and stirring steps.

Benefits of technology

The high-temperature resistance, adhesion and mechanical properties of the resin are improved, ensuring that it is not easy to brittle and deform under high temperature conditions, and has better adhesion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of UV curing resin, and discloses high-temperature-resistant UV curing resin and a preparation method thereof. The UV curing resin prepared by the invention is prepared from the following components in parts by weight: 20 to 30 parts of acrylic resin, 30 to 40 parts of urethane acrylate, 15 to 25 parts of modified acrylic resin, 4 to 8 parts of trimethylolpropane triacrylate, 3 to 10 parts of reinforcing filler, 2 to 3 parts of photoinitiator, 0.3 to 0.5 part of defoaming agent and 0.5 to 1 part of flatting agent. The coating is prepared by taking acrylic resin, polyurethane acrylic resin and modified acrylic resin as base resin, adding a reinforcing filler, a functional additive and the like, and stirring and mixing, wherein the reinforcing filler is added, so that the high temperature resistance and the mechanical property of the matrix are improved; the modified acrylic resin is added, so that the wettability of the matrix is improved, and the adhesive force of the matrix is further improved. Therefore, the UV-cured resin can be widely applied to the fields of coatings, printing ink, adhesives and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of UV curing resins, and in particular to a high temperature resistant UV curing resin and a preparation method thereof. Background Art

[0002] UV curing resin is a resin that can be cured quickly under ultraviolet light. It is mainly composed of photoactive prepolymers, active diluents and photosensitizers, including epoxy acrylates, polyurethane acrylates, polyester acrylates and amino acrylates. UV curing resin is milder, more environmentally friendly and cheaper. It can initiate the polymerization of various polymer materials such as olefins, epoxy compounds or unsaturated resins through photoinitiators. With the development of UV curing technology, the controllability of the polymerization process has increased significantly, and its application is becoming more and more extensive, such as in the fields of coatings, inks and adhesives.

[0003] As the application of UV curing resin becomes more and more widespread, some of its properties no longer meet the actual needs. For example, UV curing resin will change color, become brittle, crack, and damage the substrate under high temperature, which will affect the product quality and appearance. High temperature may also cause the resin to turn yellow or darken, reducing the transparency and appearance of the product. In addition, the poor wettability of the resin will cause the adhesion of the cured film to be limited, and it is easy to fall off. In view of the above shortcomings, the preparation of a UV curing resin with high temperature resistance and good adhesion is what current researchers need to consider. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a high temperature resistant UV curing resin and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A high temperature resistant UV curable resin comprises the following raw materials in parts by weight: 20-30 parts of acrylic resin, 30-40 parts of polyurethane acrylate, 15-25 parts of modified acrylic resin, 4-8 parts of trimethylolpropane triacrylate, 3-10 parts of reinforcing filler, 2-3 parts of photoinitiator, 0.3-0.5 parts of defoamer, and 0.5-1 parts of leveling agent; Furthermore, the photoinitiator is photoinitiator TPO, the defoamer is polydimethylsiloxane, and the leveling agent is BYK-333; The reinforcing filler is prepared by the following steps: Step A1, mixing glass fiber powder and polyvinyl alcohol in deionized water, stirring evenly, heating to 90-100°C, keeping the temperature for reaction for 30-50min, cooling to 45-55°C, adding silicone oil and sodium dodecyl sulfate, stirring for 1-2h, adding glyoxal and 10wt% hydrochloric acid, reacting for 0.5-1.5h, centrifuging, washing, and drying to obtain modified glass fiber; Step A2, uniformly dispersing the modified glass fiber in deionized water, adding melamine, and heating to 50-60° C. and stirring to react for 3-5 hours, then adding 10 mg / mL sodium cyanoborohydride solution to react for 1-2 hours, centrifuging, washing, and drying to obtain a reinforced filler; Further, in step A1, the amount ratio of glass fiber powder, polyvinyl alcohol, deionized water, silicone oil, sodium dodecyl sulfate, glyoxal and hydrochloric acid is 1-3 g: 2-5 g: 50 mL: 30-50 mL: 1.5-3 g: 0.2-1 g: 6-10 mL; Furthermore, in step A2, the usage ratio of the modified glass fiber, deionized water, melamine and sodium cyanoborohydride solution is 1-3 g:50 mL:0.5-1.5 g:5-10 mL.

[0006] The modified acrylic resin is prepared by the following steps: Step B1, under nitrogen conditions, diethylenetriamine and 4-trifluoromethylbenzoic acid are evenly dispersed in N,N-dimethylformamide, the temperature is raised to 180-200°C, condensed and refluxed for reaction for 4-6 hours, and then the temperature is raised to 220°C to continue the reaction for 1.5-2.5 hours, and rotary evaporated to obtain intermediate 1; Step B2, under nitrogen, add methanol to the intermediate product 1, mix and stir evenly, then add methyl acrylate dropwise within 0.5-1.5 hours, then raise the temperature to 30-40° C., react for 4-5 hours, and rotary evaporate to obtain the intermediate product 2; Step B3, 5-aminoisophthalic acid was mixed and stirred in N, N-dimethylformamide, recorded as 5-aminoisophthalic acid solution; under nitrogen conditions, N, N-dimethylformamide was added to the intermediate product 2 and mixed and stirred evenly, and the temperature was lowered to 0°C, and then the 5-aminoisophthalic acid solution was slowly added and stirred for 20 minutes, and then the temperature was raised to 120-140°C for reaction for 2-3 hours, and the carboxyl-terminated product was obtained by rotary evaporation and drying; Step B4, add bisphenol A epoxy resin, acrylic acid, carboxyl-terminated product, triphenylphosphine and p-methoxyphenol into a flask in sequence, and stir in an oil bath at 85-95° C. for 20-40 min, then raise the temperature to 110° C., test the acid value of the system every half an hour until the acid value is less than 1 mg·KOH / g, and terminate the reaction to obtain a modified acrylic resin; Further, in step B1, the usage ratio of diethylenetriamine, 4-trifluoromethylbenzoic acid and N,N-dimethylformamide is 0.01-0.02 mol: 0.02-0.04 mol: 100 mL; Further, the usage ratio of methyl acrylate, methanol in step B2 and diethylenetriamine in step B1 is 0.012-0.025 mol:100 mL:0.01-0.02 mol; Further, the amount ratio of 5-aminoisophthalic acid solution, N,N-dimethylformamide and methyl acrylate in step B2 in step B3 is 100mL:100mL:0.012-0.025mol, and the amount ratio of 5-aminoisophthalic acid and N,N-dimethylformamide in the 5-aminoisophthalic acid solution is 0.01-0.02mol:100mL; Furthermore, in step B4, the usage ratio of bisphenol A epoxy resin, acrylic acid, terminal carboxyl product, triphenylphosphine and p-methoxyphenol is 15-25g: 3-5g: 2-4g: 0.05-0.15g: 0.01-0.02g.

[0007] A method for preparing a high temperature resistant UV curable resin comprises the following steps: Weigh the raw materials by weight, mix the acrylic resin, polyurethane acrylate and modified acrylic resin at 50-60°C and stir evenly, then add reinforcing filler, photoinitiator, defoamer and leveling agent and stir for 10 minutes, then stir for 2-3 hours under nitrogen and 50°C, filter, and obtain the high temperature resistant UV curing resin.

[0008] Beneficial effects of the present invention: The UV curable resin prepared by the present invention is prepared by mixing acrylic resin, polyurethane acrylic resin and modified acrylic resin as base resins, adding reinforcing fillers, functional additives and the like; wherein the addition of reinforcing fillers improves the high temperature resistance and mechanical properties of the base; the addition of modified acrylic resin improves the wettability of the base, thereby improving the adhesion of the base. Therefore, the UV curable resin of the present invention can be widely used in the fields of coatings, inks, adhesives, etc.

[0009] The reinforcing filler is based on glass fiber, with polyvinyl alcohol coated on its surface, and then the hydroxyl groups in the polyvinyl alcohol film layer react with the aldehyde groups in glyoxal to generate modified glass fiber; and then the aldehyde groups on the surface of the modified glass fiber react with the amino groups in melamine to obtain the reinforcing filler. The introduction of reinforcing fillers can not only improve the high temperature resistance of the matrix, but also improve the mechanical properties of the matrix and reduce the production cost of the matrix. Among them, glass fiber with high temperature resistance can improve the high temperature resistance of the matrix, because its presence can enable the matrix to maintain a stable structure and performance in a high temperature environment, and is not easy to become brittle and deformed. The presence of the polyvinyl alcohol film layer can improve the dispersion of the glass fiber in the matrix and reduce the agglomeration of the glass fiber in the matrix. At the same time, it can also utilize its excellent flexibility to improve the mechanical properties of the glass fiber and reduce the brittleness, cracking, deformation and other phenomena caused by external forces on the matrix. In addition, the introduction of melamine further improves the high temperature resistance of the matrix, because its unique triazine structure makes it have good stability at high temperatures. At the same time, the remaining amino groups on the surface of the reinforcing filler can also react with the active groups (epoxy groups, carboxyl groups) in the resin to form a cross-linked structure, thereby improving the strength of the resin.

[0010] In the modified acrylic resin, the intermediate product 1 is first synthesized by the amidation reaction of diethylenetriamine and 4-trifluoromethylbenzoic acid; the secondary amine in the intermediate product 1 is reacted with the double bond in methyl acrylate to obtain the intermediate product 2; the ester group in the intermediate product 2 is reacted with the amino group in 5-aminoisophthalic acid to obtain a carboxyl-terminated product; finally, the carboxyl-terminated product is used to extend the side chain of the epoxy resin and capped with acrylic acid to obtain the modified epoxy resin. The introduction of modified epoxy resin not only has the excellent corrosion resistance, heat resistance and adhesion of epoxy resin, but also can participate in the ultraviolet light curing process of the matrix to improve the light curing speed; the fluorine element introduced into the side chain forms a CF bond with high bond energy, so that the resin can still maintain stable performance in a high temperature environment, and at the same time, the mutual repulsion between fluorine atoms is utilized to shield and protect the CC main chain, thereby improving the chemical corrosion resistance of the resin; and the amide bond contained in the side chain can synergistically act with the fluorine element to improve the wettability of the matrix, because the fluorine element can reduce the surface tension difference between the matrix and the substrate, and improve the wetting ability of the matrix to different substrates, and the polar groups in the amide bond can interact with the polar groups on the surface of the substrate to form a strong intermolecular force, thereby enhancing the wettability of the matrix, and then improving the adhesion and durability of the resin to the substrate surface. DETAILED DESCRIPTION

[0011] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0012] Example 1: The reinforced filler is prepared by the following steps: Step A1, 1g of glass fiber powder and 2g of polyvinyl alcohol were mixed and stirred in 50mL of deionized water, heated to 90°C, kept warm for 30min, then cooled to 45°C, 30mL of silicone oil and 1.5g of sodium dodecyl sulfate were added, stirred for 1h, 0.2g of glyoxal and 6mL of 10wt% hydrochloric acid were added, reacted for 0.5h, centrifuged, washed, and dried to obtain modified glass fiber; Step A2, evenly disperse 1g of modified glass fiber in 50mL of deionized water, add 0.5g of melamine, heat to 50°C and stir to react for 3h, then add 5mL of 10mg / mL sodium cyanoborohydride solution and react for 1h, centrifuge, wash and dry to obtain a reinforced filler.

[0013] The modified acrylic resin is prepared by the following steps: Step B1, under nitrogen conditions, 0.01 mol of diethylenetriamine and 0.02 mol of 4-trifluoromethylbenzoic acid were evenly dispersed in 100 mL of N,N-dimethylformamide, heated to 180°C, condensed and refluxed for reaction for 4 hours, then heated to 220°C and continued to react for 1.5 hours, and rotary evaporated to obtain intermediate 1; Step B2, under nitrogen, add 100 mL of methanol to the intermediate product 1, mix and stir evenly, then add 0.012 mol of methyl acrylate dropwise within 0.5 h, then heat to 30° C., react for 4 h, and rotary evaporate to obtain the intermediate product 2; Step B3, 0.01 mol of 5-aminoisophthalic acid was mixed and stirred in 100 mL of N, N-dimethylformamide, recorded as 5-aminoisophthalic acid solution; under nitrogen conditions, 100 mL of N, N-dimethylformamide was added to the intermediate product 2 and mixed and stirred evenly, and the temperature was lowered to 0°C, and then 100 mL of 5-aminoisophthalic acid solution was slowly added and stirred for 20 minutes, and then the temperature was raised to 120°C for reaction for 2 hours, and then rotary evaporated and dried to obtain a carboxyl-terminated product; Step B4: 15 g of bisphenol A epoxy resin, 3 g of acrylic acid, 2 g of terminal carboxyl product, 0.05 g of triphenylphosphine and 0.01 g of p-methoxyphenol are added to a flask in sequence, and stirred in an 85° C. oil bath for 20 min, then heated to 110° C., and the acid value of the system is tested every half hour until the acid value is <1 mg·KOH / g, and the reaction is terminated to obtain a modified acrylic resin.

[0014] Example 2: The reinforced filler is prepared by the following steps: Step A1, 2g of glass fiber powder and 3.5g of polyvinyl alcohol were mixed and stirred evenly in 50mL of deionized water, heated to 95°C, kept warm for reaction for 40min, then cooled to 50°C, 40mL of silicone oil and 2.2g of sodium dodecyl sulfate were added, stirred for 1.5h, 0.5g of glyoxal and 8mL of 10wt% hydrochloric acid were added, reacted for 1h, centrifuged, washed, and dried to obtain modified glass fiber; Step A2, disperse 2g of modified glass fiber evenly in 50mL of deionized water, add 1.1g of melamine, heat to 55°C and stir to react for 4h, then add 7.5mL of 10mg / mL sodium cyanoborohydride solution to react for 1.5h, centrifuge, wash and dry to obtain a reinforced filler.

[0015] The modified acrylic resin is prepared by the following steps: Step B1, under nitrogen conditions, 0.015 mol of diethylenetriamine and 0.03 mol of 4-trifluoromethylbenzoic acid were evenly dispersed in 100 mL of N,N-dimethylformamide, heated to 190°C, condensed and refluxed for reaction for 5 h, then heated to 220°C and continued to react for 2 h, and rotary evaporated to obtain intermediate 1; Step B2, under nitrogen, add 100 mL of methanol to the intermediate product 1, mix and stir evenly, then add 0.018 mol of methyl acrylate dropwise within 1 hour, then heat to 35° C., react for 4.5 hours, and rotary evaporate to obtain the intermediate product 2; Step B3, 0.015 mol of 5-aminoisophthalic acid was mixed and stirred in 100 mL of N, N-dimethylformamide, recorded as 5-aminoisophthalic acid solution; under nitrogen conditions, 100 mL of N, N-dimethylformamide was added to the intermediate product 2 and mixed and stirred evenly, and the temperature was lowered to 0°C, and then 100 mL of 5-aminoisophthalic acid solution was slowly added and stirred for 20 minutes, and then the temperature was raised to 130°C for reaction for 2.5 hours, and the carboxyl-terminated product was obtained by rotary evaporation and drying; Step B4: 20 g of bisphenol A epoxy resin, 4 g of acrylic acid, 3 g of terminal carboxyl product, 0.1 g of triphenylphosphine and 0.015 g of p-methoxyphenol are added to a flask in sequence, and stirred in an oil bath at 90° C. for 30 min, then heated to 110° C., and the acid value of the system is tested every half hour until the acid value is <1 mg·KOH / g, and the reaction is terminated to obtain a modified acrylic resin.

[0016] Example 3: The reinforced filler is prepared by the following steps: Step A1, 3g of glass fiber powder and 5g of polyvinyl alcohol were mixed and stirred evenly in 50mL of deionized water, heated to 100°C, kept warm for reaction for 50min, then cooled to 55°C, 50mL of silicone oil and 3g of sodium dodecyl sulfate were added, stirred for 2h, 1g of glyoxal and 10mL of 10wt% hydrochloric acid were added, reacted for 1.5h, centrifuged, washed, and dried to obtain modified glass fiber; Step A2, disperse 3g of modified glass fiber evenly in 50mL of deionized water, add 1.5g of melamine, heat to 60°C and stir to react for 5h, then add 10mL of 10mg / mL sodium cyanoborohydride solution and react for 2h, centrifuge, wash and dry to obtain a reinforced filler.

[0017] The modified acrylic resin is prepared by the following steps: Step B1, under nitrogen conditions, 0.02 mol of diethylenetriamine and 0.04 mol of 4-trifluoromethylbenzoic acid were evenly dispersed in 100 mL of N,N-dimethylformamide, heated to 200°C, condensed and refluxed for reaction for 6 hours, then heated to 220°C and continued to react for 2.5 hours, and rotary evaporated to obtain intermediate 1; Step B2, under nitrogen, add 100 mL of methanol to the intermediate product 1, mix and stir evenly, then add 0.025 mol of methyl acrylate dropwise within 1.5 h, then heat to 40° C., react for 5 h, and rotary evaporate to obtain the intermediate product 2; Step B3, 0.02 mol of 5-aminoisophthalic acid was mixed and stirred in 100 mL of N, N-dimethylformamide, recorded as 5-aminoisophthalic acid solution; under nitrogen conditions, 100 mL of N, N-dimethylformamide was added to the intermediate product 2 and mixed and stirred evenly, and the temperature was lowered to 0°C, and then 100 mL of 5-aminoisophthalic acid solution was slowly added and stirred for 20 minutes, and then the temperature was raised to 140°C for reaction for 3 hours, and then rotary evaporated and dried to obtain a carboxyl-terminated product; Step B4: 25 g of bisphenol A epoxy resin, 5 g of acrylic acid, 4 g of terminal carboxyl product, 0.15 g of triphenylphosphine and 0.02 g of p-methoxyphenol are added to a flask in sequence, and stirred in an oil bath at 95° C. for 40 min, then heated to 110° C., and the acid value of the system is tested every half hour until the acid value is <1 mg·KOH / g, and the reaction is terminated to obtain a modified acrylic resin.

[0018] Embodiment 4: A method for preparing a high temperature resistant UV curable resin comprises the following steps: 20 parts of acrylic resin, 30 parts of polyurethane acrylate, 15 parts of modified acrylic resin prepared in Example 1, 4 parts of trimethylolpropane triacrylate, 3 parts of reinforcing filler prepared in Example 1, 2 parts of photoinitiator TPO, 0.3 parts of polydimethylsiloxane, and 0.5 parts of leveling agent BYK-333; The raw materials were weighed by weight, and the acrylic resin, polyurethane acrylate and the modified acrylic resin prepared in Example 1 were mixed and stirred evenly at 50° C., and then the reinforcing filler, photoinitiator TPO, polydimethylsiloxane and leveling agent BYK-333 prepared in Example 1 were added and stirred for 10 minutes, and then stirred for 2 hours under nitrogen at 50° C., and filtered to obtain a high temperature resistant UV curing resin.

[0019] Embodiment 5: A method for preparing a high temperature resistant UV curable resin comprises the following steps: 25 parts of acrylic resin, 35 parts of polyurethane acrylate, 20 parts of modified acrylic resin prepared in Example 2, 6 parts of trimethylolpropane triacrylate, 6 parts of reinforcing filler prepared in Example 2, 2.5 parts of photoinitiator TPO, 0.4 parts of polydimethylsiloxane, and 0.8 parts of leveling agent BYK-333; The raw materials were weighed by weight, and the acrylic resin, polyurethane acrylate and the modified acrylic resin prepared in Example 2 were mixed and stirred evenly at 55° C., and then the reinforcing filler, photoinitiator TPO, polydimethylsiloxane and leveling agent BYK-333 prepared in Example 2 were added and stirred for 10 minutes, and then stirred for 2.5 hours under nitrogen and 50° C., and filtered to obtain a high temperature resistant UV curing resin.

[0020] Embodiment 6: A method for preparing a high temperature resistant UV curable resin comprises the following steps: 30 parts of acrylic resin, 40 parts of polyurethane acrylate, 15 parts of modified acrylic resin prepared in Example 3, 8 parts of trimethylolpropane triacrylate, 10 parts of reinforcing filler prepared in Example 3, 3 parts of photoinitiator TPO, 0.5 parts of polydimethylsiloxane, 1 part of leveling agent BYK-333; The raw materials were weighed by weight, and the acrylic resin, polyurethane acrylate and the modified acrylic resin prepared in Example 3 were mixed and stirred evenly at 60° C., and then the reinforcing filler, photoinitiator TPO, polydimethylsiloxane and leveling agent BYK-333 prepared in Example 3 were added and stirred for 10 minutes, and then stirred for 3 hours under nitrogen and 50° C., and filtered to obtain a high temperature resistant UV curing resin.

[0021] Comparative Example 1: This comparative example is a UV curable resin. The difference from Example 6 is that glass fiber powder is used instead of the reinforcing filler prepared in Example 3, and the rest is the same.

[0022] Comparative Example 2: This comparative example is a UV curable resin. The difference from Example 6 is that epoxy resin is used instead of the modified acrylic resin prepared in Example 3, and the rest are the same.

[0023] The UV curable resin prepared in Examples 4-6 and Comparative Examples 1-2 was sprayed on a transparent PC substrate and placed in a light curing machine at 800 mJ / cm 2 The surface is cured and the film is formed, and the performance test is carried out: Adhesion test: refer to national standard GB / T 9286-1998; Hardness test: refer to national standard GB / T 6739-2006; High temperature resistance test: bake the sample at 250℃ for 5 minutes, and observe whether the surface of the sample falls off or cracks; The test results are shown in Table 1: Table 1: Performance test results

[0024] As can be seen from Table 1, after the adhesion, pencil hardness and high temperature resistance tests, the adhesion grade of the UV-curable resin prepared by the present invention is 1, the pencil hardness is 2H, and there is no shedding or cracking under high temperature conditions, indicating that the UV-curable resin has excellent adhesion, pencil hardness and high temperature resistance.

[0025] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A high temperature resistant UV curable resin, characterized in that: The invention comprises the following raw materials in parts by weight: 20-30 parts of acrylic resin, 30-40 parts of polyurethane acrylate, 15-25 parts of modified acrylic resin, 4-8 parts of trimethylolpropane triacrylate, 3-10 parts of reinforcing filler, 2-3 parts of photoinitiator, 0.3-0.5 parts of defoamer and 0.5-1 parts of leveling agent; The reinforcing filler is prepared by the following steps: Step A1, mixing glass fiber powder and polyvinyl alcohol in deionized water, stirring evenly, heating to 90-100°C, keeping the temperature for reaction for 30-50min, cooling to 45-55°C, adding silicone oil and sodium dodecyl sulfate, stirring for 1-2h, adding glyoxal and 10wt% hydrochloric acid, reacting for 0.5-1.5h, centrifuging, washing, and drying to obtain modified glass fiber; Step A2, uniformly disperse the modified glass fiber in deionized water, add melamine, and heat to 50-60° C. and stir to react for 3-5 hours, then add 10 mg / mL sodium cyanoborohydride solution to react for 1-2 hours, centrifuge, wash, and dry to obtain a reinforced filler.

2. A high temperature resistant UV curable resin according to claim 1, characterized in that: In step A1, the usage ratio of glass fiber powder, polyvinyl alcohol, deionized water, silicone oil, sodium dodecyl sulfate, glyoxal and hydrochloric acid is 1-3 g: 2-5 g: 50 mL: 30-50 mL: 1.5-3 g: 0.2-1 g: 6-10 mL.

3. A high temperature resistant UV curable resin according to claim 1, characterized in that: In step A2, the usage ratio of the modified glass fiber, deionized water, melamine and sodium cyanoborohydride solution is 1-3 g:50 mL:0.5-1.5 g:5-10 mL.

4. The high temperature resistant UV curable resin according to claim 1, characterized in that: The photoinitiator is photoinitiator TPO, the defoamer is polydimethylsiloxane, and the leveling agent is BYK-333.

5. The high temperature resistant UV curing resin according to claim 1, characterized in that: The modified acrylic resin is prepared by the following steps: Step B1, under nitrogen conditions, diethylenetriamine and 4-trifluoromethylbenzoic acid are evenly dispersed in N,N-dimethylformamide, the temperature is raised to 180-200°C, condensed and refluxed for reaction for 4-6 hours, and then the temperature is raised to 220°C to continue the reaction for 1.5-2.5 hours, and rotary evaporated to obtain intermediate 1; Step B2, under nitrogen, add methanol to the intermediate product 1, mix and stir evenly, then add methyl acrylate dropwise within 0.5-1.5 hours, then raise the temperature to 30-40° C., react for 4-5 hours, and rotary evaporate to obtain the intermediate product 2; Step B3, 5-aminoisophthalic acid was mixed and stirred in N, N-dimethylformamide, recorded as 5-aminoisophthalic acid solution; under nitrogen conditions, N, N-dimethylformamide was added to the intermediate product 2 and mixed and stirred evenly, and the temperature was lowered to 0°C, and then the 5-aminoisophthalic acid solution was slowly added and stirred for 20 minutes, and then the temperature was raised to 120-140°C for reaction for 2-3 hours, and the carboxyl-terminated product was obtained by rotary evaporation and drying; Step B4, add bisphenol A epoxy resin, acrylic acid, terminal carboxyl product, triphenylphosphine and p-methoxyphenol into a flask in sequence, and stir in an oil bath at 85-95°C for 20-40 minutes, then raise the temperature to 110°C, test the acid value of the system every half an hour until the acid value is <1 mg·KOH / g, and terminate the reaction to obtain a modified acrylic resin.

6. A high temperature resistant UV curable resin according to claim 5, characterized in that: In step B1, the usage ratio of diethylenetriamine, 4-trifluoromethylbenzoic acid and N,N-dimethylformamide is 0.01-0.02 mol: 0.02-0.04 mol: 100 mL.

7. The high temperature resistant UV curing resin according to claim 5, characterized in that: The usage ratio of methyl acrylate, methanol in step B2 and diethylenetriamine in step B1 is 0.012-0.025 mol:100 mL:0.01-0.02 mol.

8. The high temperature resistant UV curable resin according to claim 5, characterized in that: The usage ratio of 5-aminoisophthalic acid solution, N,N-dimethylformamide and methyl acrylate in step B3 is 100mL:100mL:0.012-0.025mol, and the usage ratio of 5-aminoisophthalic acid and N,N-dimethylformamide in the 5-aminoisophthalic acid solution is 0.01-0.02mol:100mL.

9. The high temperature resistant UV curable resin according to claim 5, characterized in that: In step B4, the usage ratio of bisphenol A epoxy resin, acrylic acid, terminal carboxyl product, triphenylphosphine and p-methoxyphenol is 15-25g: 3-5g: 2-4g: 0.05-0.15g: 0.01-0.02g.

10. A method for preparing the high temperature resistant UV curable resin according to any one of claims 1 to 9, characterized in that: The following steps are involved: Weigh the raw materials by weight, mix the acrylic resin, polyurethane acrylate and modified acrylic resin at 50-60°C and stir evenly, then add reinforcing filler, photoinitiator, defoamer and leveling agent and stir for 10 minutes, then stir for 2-3 hours under nitrogen and 50°C, filter, and obtain the high temperature resistant UV curing resin.

Citation Information

Patent Citations

  • Ultraviolet curing processing agent

    CN102199377A

  • UV photocuring transfer printing material

    CN113136116A

  • Ultraviolet curing color glue and preparation method thereof

    CN113462345A

  • Curable resin composition and cured product thereof

    JP2003183401A

Cited By

  • Modified acrylic acid high-temperature-resistant optical cement and preparation method thereof

    CN120944490A

  • Modified acrylic high-temperature-resistant optical adhesive and preparation method thereof

    CN120944490B